Temperature-dependent Crystallization of MoS(2) Nanoflakes on Graphene Nanosheets for Electrocatalysis - Guo, Xiaoru (Nanoscale Res Lett, 2017)
This work primarily studies the crystallization condition of molybdenum disulfide (MoS(2)) in MoS(2)/graphene hybrids by a temperature-varying hydrothermal method from 150 to 240 °C. Flower-like MoS(2) nanoflakes were successfully grown on graphene nanosheets and characterized to understand the temperature-dependent crystallization process and the electrochemical performance. The highest electrocatalytic efficiency for both the dye-sensitized solar cell and the hydrogen evolution reaction was obtained by preparing the hybrid at 180 °C, which benefits from balanced high reactivity and high conductivity. This research leads to a better understanding of temperature dependence of MoS(2) crystallization and offers guidelines for better catalytic material design. [Figure: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s11671-017-2248-9) contains supplementary material, which is available to authorized users.